PROVIDING HOUSEHOLD CUSTOMERS WITH SMART METERING DATA ON MOBILE DEVICES - Hakobyan, Syuzanna; Kohlbrecher, Jan-Philipp; Pickert, Johannes; Grossmann, Uwe (International Journal of Computing, 2011)
One option for reducing carbon dioxide emissions is the future use of renewable instead of fossil resources. A consistent prerequisite is the optimization of household customers’ energy consumption behavior. The suitable visualization of energy data, corresponding costs and tariff information on mobile devices is essential to achieve this goal. Energy data are acquired by a smart meter and transferred over wireless networks to a mobile device to provide the customer with relevant information about his current energy usage. The household customer is hence enabled to manage his energy consumption, to hold the optimal load and meet the optimum price. Suitable typs of visualization, specific for different tariffs, are identified and presented together with necessary technologies and methods for communication and data access and delivery.